DEVELOPING A HYBRID GOVERNANCE MODEL THAT COMBINES TRADITIONAL RELIGIOUS AUTHORITY WITH MODERN EDUCATIONAL MANAGEMENT PRINCIPLES IN INDONESIAN PESANTRENS - Wahyudin (Adisam Publisher, 2026)
Indonesian Islamic boarding schools are facing a critical transformation as they strive to strike a balance between upholding traditional religious authority and adopting contemporary management practices in response to globalisation, regulatory reform and the modernisation of education. This study demonstrates that Islamic boarding schools operate within a unique hybrid governance model, which neither entirely abandons tradition nor fully adopts a bureaucratic structure, but rather creates a dynamic balance between kiai-centred authority and a professional management system. Theoretically, this phenomenon represents an institutional adaptation shaped by three interrelated factors: the resilience of moral and charismatic authority rooted in Islamic spiritual values; the strategic integration of formal governance mechanisms to ensure accountability and sustainability; and the selective adoption of modern educational practices whilst preserving religious identity. This research examines how Islamic boarding schools can strengthen their institutional credibility through transparent governance whilst preserving the cultural authenticity that defines their mission in shaping Muslim character and knowledge. Using a systematic literature review of over 30 academic sources examining pesantren governance, management practices and institutional transformation between 2020 and 2025, this study identifies patterns of how traditional authorities operate as a governance resource rather than as an obstacle to professionalisation. Key findings indicate that successful pesantren integrate Qur’anic and Islamic values (amanah, musyawarah, ihsan) into measurable performance systems, establish collaborative management structures involving various stakeholders whilst maintaining the leadership of the kiai, and balance financial sustainability through diversified funding with transparent reporting. Notably, pesantren implementing a hybrid governance model demonstrate improved educational quality, greater accountability without compromising religious authenticity, and greater institutional resilience to external pressures. This study concludes that hybrid governance in pesantren is not a transitional phase towards full modernisation, but rather a distinctive institutional form appropriate to the context of religion-based education. This research contributes to educational management theory by demonstrating how religious authority and professional management can be integrated rather than viewed as conflicting forces; it provides insights applicable to Islamic educational institutions globally; and it recommends that policymakers support a hybrid governance framework rather than imposing a uniform bureaucratic model on faith-based institutions.